Commensal Neisseria cinerea impairs Neisseria meningitidis microcolony development and reduces pathogen colonisation of epithelial cells. - Rafael Custodio; Errin Johnson; Guangyu Liu; Christoph M Tang; Rachel M Exley (PLoS Pathogens, 2020)
It is increasingly being recognised that the interplay between commensal and pathogenic bacteria can dictate the outcome of infection. Consequently, there is a need to understand how commensals interact with their human host and influence pathogen behaviour at epithelial surfaces. Neisseria meningitidis, a leading cause of sepsis and meningitis, exclusively colonises the human nasopharynx and shares this niche with several other Neisseria species, including the commensal Neisseria cinerea. Here, we demonstrate that during adhesion to human epithelial cells N. cinerea co-localises with molecules that are also recruited by the meningococcus, and show that, similar to N. meningitidis, N. cinerea forms dynamic microcolonies on the cell surface in a Type four pilus (Tfp) dependent manner. Finally, we demonstrate that N. cinerea colocalises with N. meningitidis on the epithelial cell surface, limits the size and motility of meningococcal microcolonies, and impairs the effective colonisation of epithelial cells by the pathogen. Our data establish that commensal Neisseria can mimic and affect the behaviour of a pathogen on epithelial cell surfaces.